Overview of COVID-19 Vaccine Development Strategy - Katerine Junaidi; Dewi Wahyu Fitrina; Fenty Anggrainy; Deddy Herman (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was identified as the cause of coronavirus disease 20019 (COVID19) pandemic which first emerged in December 2019 in Wuhan city, China. Currently, a vaccine is urgently needed to control the COVID-19 pandemic. Several vaccine candidates are under development and some are in the final stage of clinical trials. The COVID-19 vaccination aims to reduce morbidity and mortality rates, achieve herd immunity to prevent and protect the society, strengthen the health system, maintain productivity and minimize social and economic impacts. Before approval, vaccines have to undergo several clinical trials to ensure its safety profile, efficacy, duration of immune system resistance, and adverse effect. Various strategies have been used in the development of vaccines including viral vector vaccines, nucleic acid vaccines, inactivated virus, live attenuated virus, subunit protein¸and virus-like particle vaccine. Each strategy has its own advantages and disadvantages.